2022
DOI: 10.1101/2022.03.08.22272101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Not all mosquitoes are created equal: incriminating mosquitoes as vectors of arboviruses

Abstract: The globalization of mosquito-borne arboviral diseases has placed more than half of the human population at risk. Understanding arbovirus ecology, including the role individual mosquito species play in virus transmission cycles, is critical for limiting disease. Canonical virus-vector groupings, such as Aedes- or Culex-associated flaviviruses, have historically been defined using phylogenetic associations, virus isolation in the field, and mosquito feeding patterns. These associations less frequently rely on v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Finally, our study highlights that a substantial breadth and depth of vector competence data are published every year in the peer-reviewed literature, but currently, the results of these experiments have no standardized home. Other recent studies highlight that synthesis of these data is possible, despite the complexity of metadata required to describe variation in experimental protocols (Kain et al, 2022); however, our study highlights the challenges of recovering "findable" data from the vector competence literature. Limitations we encountered included: (1) several databases capture these studies (and older studies in particular appear to be missing from Web of Science); (2) keywords we used may not have captured all of the relevant studies, due to variable terminology; (3) a handful of non-English language publications-in particular, Spanish and French language publications from Latin America and Africa, respectively-will not have been captured by our search terms; and ( 4) not all studies reported reusable experimental results and metadata.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, our study highlights that a substantial breadth and depth of vector competence data are published every year in the peer-reviewed literature, but currently, the results of these experiments have no standardized home. Other recent studies highlight that synthesis of these data is possible, despite the complexity of metadata required to describe variation in experimental protocols (Kain et al, 2022); however, our study highlights the challenges of recovering "findable" data from the vector competence literature. Limitations we encountered included: (1) several databases capture these studies (and older studies in particular appear to be missing from Web of Science); (2) keywords we used may not have captured all of the relevant studies, due to variable terminology; (3) a handful of non-English language publications-in particular, Spanish and French language publications from Latin America and Africa, respectively-will not have been captured by our search terms; and ( 4) not all studies reported reusable experimental results and metadata.…”
Section: Discussionmentioning
confidence: 90%
“…Experimental studies simplify real-world complexities of transmission, and can be used to test not only the basic compatibility of a given virus and arthropod vector species, but also vector competence—the relative ability of arthropod vectors to be infected by a virus and then disseminate and transmit it to a susceptible host (Mellor, 2000). Despite arboviruses’ evolutionary tendencies towards broad host and vector range (Ciota and Kramer, 2010; Coffey et al, 2008; Kreuder Johnson et al, 2015), there are complex genetic underpinnings that govern vector competence (Beerntsen et al, 2000), which can manifest as variation in competence between closely related species of vector (Kain et al, 2022) or even among populations of the same species (Souza-Neto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have begun to scale this gap: one study compiled a table of results from several dozen studies of Aedes aegypti and various arboviruses (see Table 3) 24 . More recently, another study compiled a dataset of 80 experiments that tested 115 combinations of Australian mosquitoes and arboviruses, and analyzed biological signals in the aggregated data 25 . These types of efforts are painstaking, requiring substantial manual curation of metadata, and hundreds more experiments are reported in the literature, yet remain unsynthesized due to this barrier 1 .…”
Section: Discussionmentioning
confidence: 99%